Designing Women: Learning from Feminist Legacies and the Women-In-Games Movement - Schoemann, Sarah (Georgia Institute of Technology, 2021)
In 2019 the video games industry was rocked by a slew of high-profile sexual harassment and assault allegations that some called the #MeToo movement of the games world, but to many these revelations came as no surprise. From the 2004 EA Spouse controversy to the 2014 #Gamergate harassment campaign the games industry has long been known for harboring an at times toxic atmosphere of exploitation and discrimination. This project looks at a handful of Women-In-Games organizations that set out to change the experience of women in the industry by helping newcomers to gain high tech skills and to supporting early career professionals through mentorship and community building. Along the way, it combines the study of these Women-In-Games organizations with a years-long collaboration bringing video games to the US' oldest feminist bookstore, Charis Books & More in Atlanta, GA. Through examining the work and values of two types of organizations devoted to women's equality, one a historic feminist movement-building space and the others, contemporary interventions into the professional games and tech industry, this study asks the questions "What can the Women-In-Games movement learn from the rich history of feminist organizing at spaces like Charis?" "Can games play a part in feminist movement building?" and "What does the future of feminist organizing look like in the games industry?”
Keywords: Bibliographie; Irina; Nettoyer

“Frat Boy” Culture: Will the Activision Lawsuit Reform the Gaming Industry? - Lawrence, Kelsey (2021)
Keywords: Irina; games; gaming; industry; lawsuits; sexual harassment; students

A More Pixelated Union: A Look at the Path to Unionization in the Video Game Industry under Trump's National Labor Relations Board - Selfridge, William C. (2021)
Keywords: Irina

Title IX, Esports, and #EToo - Stoever, Jane K (The George Washington Law Review, 2021)
As colleges and universities increasingly award video gaming scholarships, field competitive esports teams, construct esports arenas in the centers of campuses, and promote student interaction through gaming, schools should anticipate the sexual cyberviolence, harassment, and technology-enabled abuse that commonly occur through gaming.
Keywords: Bibliographie; Irina; Nettoyer